2017
DOI: 10.1186/s12886-017-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of actin depolymerization induced by Cytochalasin D and mechanical stretch on interleukin-8 expression and JNK phosphorylation levels in human retinal pigment epithelial cells

Abstract: BackgroundThis study explores the role of actin cytoskeleton depolymerization induced by Cytochalasin D and mechanical stretch on the interleukin-8 (IL-8) expression and c-jun N-terminal kinase (JNK) phosphorylation levels in human retinal pigment epithelial (RPE) cells.MethodsA Flexcell FX-5000 Tension system was used to apply cyclic stretch to cultured human RPE cells (ARPE-19) at 0.33 Hz with 20% elongation for 0 h, 6 h or 24 h. The cells were stretched alone or pre-treated with Cytochalasin D. The redistri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
5
6
0
Order By: Relevance
“…3q, s, t) was consistent with previous reports of IL-8 and VEGF induction in human RPE cells after RPE injury [29,30]. It has previously been shown that actin polymerization activation induces IL-8 expression and different VEGF isoforms [31,32] . It is therefore possible that disrupting the actin cytoskeleton activates actin polymerization, leading to the increased expression of IL-8 and different VEGF isoforms.…”
Section: Discussionsupporting
confidence: 92%
“…3q, s, t) was consistent with previous reports of IL-8 and VEGF induction in human RPE cells after RPE injury [29,30]. It has previously been shown that actin polymerization activation induces IL-8 expression and different VEGF isoforms [31,32] . It is therefore possible that disrupting the actin cytoskeleton activates actin polymerization, leading to the increased expression of IL-8 and different VEGF isoforms.…”
Section: Discussionsupporting
confidence: 92%
“…3q, s, t) was consistent with previous reports of IL -8 and VEGF induction in human RPE cells after RPE injury [30,31]. It has previously been shown that actin polymerization activation induces IL-8 expression and different VEGF isoforms [32,33] . It is therefore possible that disrupting the actin cytoskeleton activates actin polymerization, leading to the increased expression of IL-8 and different VEGF isoforms.…”
Section: Discussionsupporting
confidence: 92%
“…3q, s, t) was consistent with previous reports of IL -8 and VEGF induction in human RPE cells after RPE injury [20,21]. It has previously been shown that actin polymerization activation induces IL-8 expression and different VEGF isoforms [22,23]. It is therefore possible that disrupting the actin cytoskeleton activates actin polymerization, leading to the increased expression of IL-8 and different VEGF isoforms.…”
supporting
confidence: 91%